Specifics of intercultural communication: professional dialogue, etiquette, appearance in the different countries; Коммуникативные аспекты языка и культуры; Ч. 3 - Akhmetov B. R. (Доклады студентов нелингвистических специальностей на круглых столах, 2015)
Заглавие с титульного экрана